2023
DOI: 10.1002/ardp.202200405
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of benzamide‐chalcone hybrids as potential c‐Met kinase and COX‐2 inhibitors

Abstract: c-Met kinase and cyclooxygenase 2 (COX-2) enzymes are two significant targets in tumor progression. Chalcone and benzamide moieties were combined using molecular hybridization to assess their potential as c-Met kinase and COX-2 inhibitors. 4-Methylbenzamide and 4-chlorobenzamide chalcone analogs were synthesized, characterized, and evaluated for antiproliferative activity on Michigan Cancer Foundation-7 (MCF-7), HT-29, MDA-MB-231, COLO-205, and A549 cell lines by sulforhodamine-B stain (SRB) assay. Following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated that the overexpression of COX-2, and subsequent production of PGE 2 , can enhance cell motility in colorectal cancer cell lines [ 12 ]. Various studies examined the antimigratory potential of COX-2 inhibitors [ 12 , 13 ]. For the natural dual COX-2 and 5-LOX inhibitor psoralidin, potent cytotoxicity against HT-29 and MCF-7 cancer cell lines, as well as attenuation of fibroblast migration caused by radiation therapy, was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that the overexpression of COX-2, and subsequent production of PGE 2 , can enhance cell motility in colorectal cancer cell lines [ 12 ]. Various studies examined the antimigratory potential of COX-2 inhibitors [ 12 , 13 ]. For the natural dual COX-2 and 5-LOX inhibitor psoralidin, potent cytotoxicity against HT-29 and MCF-7 cancer cell lines, as well as attenuation of fibroblast migration caused by radiation therapy, was demonstrated.…”
Section: Introductionmentioning
confidence: 99%